STUDI TENTANG PERANAN EKSTRAKURIKULER ROHIS DALAM MEMBENTUK BUDI PEKERTI SISWA DI SMK NEGERI 4 PEKANBARU - Duwi Julita; Gimin Gimin; Ahmad Eddison (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Extracurricular activities have a very important role in efforts to foster student attitudes, one of which is the formation of character, because the formation of manners can not only rely on the teaching and learning process in the classroom, but also the extracurricular role is needed, especially Rohis extracurricular, because in the rohis extracurricular there is religious knowledge, where religion and character are closely related, because every religion must teach goodness with the aim that the formation of student character can be achieved to the maximum. The aim of this research is: to find out how the role of the rohis extracurricular in shaping students' character in SMK Negeri 4 Pekanbaru, to find out how students behave in a rohis extracurricular at SMK Negeri 4 Pekanbaru, to find out how the influence of the rohis extracurricular in shaping students' character in SMK Negeri 4 Pekanbaru. The subjects of this study were all students who took rohis extracurricular activities at SMK Negeri 4 Pekanbaru totaling 68 people. Data collected through observation, questionnaires, interviews, and documentation. In analyzing data using quantitative descriptive techniques with statistical tests. The results showed that the role of the rohis extracurricular in shaping the character of students in SMK Negeri 4 Pekanbaru was at a very good level. Character students who take part in Rohis extracurricular activities at SMK Negeri 4 Pekanbaru are included in the excellent category. There is a significant influence in this study, because it is known that the results of a simple linear regression test between variable X and variable Y. F is obtained Fcount of 7.414 and Ftable of 3.99 indicates Fcount > Ftable, so Ho is rejected and Ha is accepted. Low effect due to 31.8%Key Words: Role, Rohis Extracurricular, Character